Observation of quantum oscillations in FIB fabricated nanowires of topological insulator (Bi2Se3). (7th February 2017) - Bhattacharyya, Biplab; Sharma, Alka; Awana, V P S; Srivastava, A K; Senguttuvan, T D; Husale, Sudhir
Abstract: In the last few years, research based on topological insulators (TIs) has been of great interest due to their intrinsic exotic fundamental properties and potential applications such as quantum computers or spintronics. The fabrication of TI nanodevices and the study of their transport properties has mostly focused on high quality crystalline nanowires or nanoribbons. Here, we report a robust approach to Bi2 Se3 nanowire formation from deposited flakes using an ion beam milling method. Fabricated Bi2 Se3 nanowire devices were employed to investigate the robustness of the topological surface state (TSS) to gallium ion doping and any deformation in the material due to the fabrication tools. We report on the quantum oscillations in magnetoresistance (MR) curves under the parallel magnetic field. The resistance versus magnetic field curves are studied and compared with Aharonov–Bohm (AB) interference effects, which further demonstrate transport through the TSS. The fabrication route and observed electronic transport properties indicate clear quantum oscillations, and these can be exploited further in studying the exotic electronic properties associated with TI-based nanodevices.